Ethanol production in switchgrass hydrolysate by ionic liquid-tolerant yeasts. (September 2019) - Sitepu, Irnayuli R.; Enriquez, Lauren L.; Nguyen, Valerie; Doyle, Carolyn; Simmons, Blake A.; Singer, Steven W.; Fry, Russell; Simmons, Christopher W.; Boundy-Mills, Kyria
Abstract: Lignocellulose pretreatment with ionic liquids (IL) enables release of fermentable sugars at yields suitable for biofuel production. However, despite extensive washing, residual IL such as 1-ethyl-3-methylimidazolium acetate ([C2 C1 Im][OAc]) is harmful to microbes and enzymes involved in downstream processes. Ionic liquid-pretreated switchgrass hydrolysate contains from 0.2 to 4% (w/v) residual [C2 C1 Im][OAc] depending on the extent of water washing. A total of 25 yeast strains including four commercial ethanologenic Saccharomyces cerevisiae strains were tested to grow and ferment sugars in stepwise screening tests, and ethanol production was measured by GC-FID. Four yeast strains produced >10 g/L ethanol in laboratory media containing [C2 C1 Im][OAc]. The highest ethanol yield of 70% of theoretical yield was achieved by Wickerhamomyces anomalus UCDFST 72-248 when grown in hydrolysate with 3.2% residual IL. The robust growth and ethanol production by this wild (non-GMO) yeast, together with general stress tolerance of the species, suggests further exploration for biotechnology applications. Graphical abstract: Unlabelled Image Highlights: Ionic liquid (IL) used in pretreatment is harmful to microbes and enzymes. A Wickerhamomyces strain produced more ethanol in residual IL than Saccharomyces . Wild non- Saccharomyces are an alternative to genetically modified Saccharomyces .